Formulation Workshop of Business Processes and Standard Operating Procedures at Medan State University - Ritonga, Winsyahputra; Yusuf, Muhammad; Karo Karo, Ichwanul Muslim (PT FORMOSA CENDEKIA GLOBAL, 2024)
The availability of effective and standardized documentation Standard Operational Procedure (SOP) and business processes of Medan State University (Unimed) creates an effective and efficient bureaucracy, maintains the quality and consistency of campus services and achieving the campus vision. In fact, there are still unstandardized SOP and business processes based on two Ministerial Regulations (PERMENPAN RB) No. 19 in 2018 and No. 35 in 2012. Due to the limited number of human resources who understand, it is necessary to improve the ability of human resources to compile effective and standardized SOP and business processes. This workshop activity reached out to all faculty and postgraduate program participants. The tool used to develop SOP and business processes is the Bizagi application